ShopeePay Dalam Perspektif Hukum Ekonomi Syariah: Kritik Atas Praktik dan Dampaknya - Latifatuzzahra; Mufidah Zahro; Dina Marni (Program Studi Hukum Ekonomi Syariah STAI As-Sunnah Deli Serdang, Sumatera Utara, 2025)
ShopeePay is one of the most widely used e-wallets by the Indonesian people in recent years. The development of fintech has made ShopeePay part of the life of modern society. ShopeePay and its installment feature offer ease of transactions. However, it raises questions related to the conformity of its practice with Islamic law.The wider this matter is, Muslims need to study the laws contained in it, to use digital wallets without hesitation. This research uses qualitative descriptive with a maslahah approach and analysis of contemporary muamalah contracts. The purpose of this study is to provide an analysis of Islamic law on the use of ShopeePay and PayLater in Muslim community transactions. This study found that there are elements of usury and ambiguity of contracts in some features of ShopeePay, which requires caution from the perspective of Islamic law.